2018
DOI: 10.1186/s13104-018-3659-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mental resilience and perceived immune functioning on the severity of alcohol hangover

Abstract: ObjectiveRecent research comparing hangover sensitive drinkers with hangover resistant drinkers has revealed that experiencing alcohol hangovers is associated with significantly poorer self-reported immune functioning (p < 0.0001). No significant difference between the groups was found on mental resilience. The objective of the current survey was to examine the association between hangover severity, perceived immune status, and mental resilience. N = 341 Dutch students, all hangover sensitive drinkers, complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
1
19
3
Order By: Relevance
“…Interestingly, the 'no hangover' group happened to give significantly higher ratings of their immune fitness and physical fitness, as compared to the two other groups. Previous studies have reported a relationship between perceived immune fitness and hangover susceptibility [31], but not with hangover severity [32]. In the current study, hangover severity scores also did not significantly correlate with the immune fitness rating in the 'hangover' group.…”
Section: Discussioncontrasting
confidence: 83%
“…Interestingly, the 'no hangover' group happened to give significantly higher ratings of their immune fitness and physical fitness, as compared to the two other groups. Previous studies have reported a relationship between perceived immune fitness and hangover susceptibility [31], but not with hangover severity [32]. In the current study, hangover severity scores also did not significantly correlate with the immune fitness rating in the 'hangover' group.…”
Section: Discussioncontrasting
confidence: 83%
“…The physiological mechanisms of hangover are not well understood, but likely involve multiple processes [61], including actual and perceived immune status [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…A simple "culprit" responsible for this range of symptoms has yet to be identified. The toxic metabolite acetaldehyde has largely gone from the system when hangover remains, although research suggests that an inflammatory response and cytokine elevation may account for some symptoms [12][13][14][15]. Changes in neurotransmitters and mitochondrial dysfunction, as well as the congeners added to different types of drink may also have a role [16].…”
Section: Introductionmentioning
confidence: 99%